Exploring the Evolution of Lateral Earth Pressure using the Distinct Element Method. (14th November 2013) - Weng, M.-C.; Cheng, C.-C.; Chiou, J.-S.
Abstract : This study adopted the distinct element method (DEM) to explore the key influencing factors on the variations of lateral earth pressure, including packing type, interior friction angle, particle stiffness and particle size. The reference parameters for the DEM model were retrieved from direct shear tests of a rod assembly. Based on the reference parameters, the evolution of lateral earth pressure is further simulated, and a parametric study was conducted. The results showed that: (1) the analysis model could effectively capture the variation of lateral earth pressure under both active and passive conditions, and the simulated failure patterns were consistent with those from the sandbox tests; (2) the greater interior friction angle ϕinterior decreased the active coefficient Ka and increased the passive coefficient Kp ; (3) increasing particle stiffness decreased the active coefficient Ka and increased the passive coefficient Kp ; (4) larger particle sizes led to a larger active coefficient Ka and a smaller passive coefficient Kp ; and (5) when the particle assembly was arranged in order, its lateral pressure was much larger than that of the randomly packed assembly.